Influence of Servicescape, Perceived Value, and Price Perception on Purchase Decisions for Membership at Fit Hub Setiabudi Semarang - Redite Cahyo Permadi; Rustono; Makmun Riyanto (Politeknik Negeri Semarang, 2025)
This study aims to analyze the influence of Servicescape, Perceived Value, and Price Perception on the Purchase Decision of membership packages at FIT HUB Setiabudi Semarang. The data were collected through questionnaires distributed to members using a 4-point Likert scale. The sampling technique applied was purposive sampling, with 123 respondents selected as participants. Data processing was conducted using SPSS version 25. Based on the results of multiple linear regression analysis, the equation obtained is Y = 0.729 + 0.235X1 + 0.279X2 + 0.272X3. The t-test results indicate that each independent variable has a significant effect on the Purchase Decision (Y). The F-test shows that the regression model is feasible, which means that Servicescape (X1), Perceived Value (X2), and Price Perception (X3) simultaneously influence the Purchase Decision (Y). The coefficient of determination (R²) is 0.668, indicating that 66.8% of the variance in Purchase Decision (Y) can be explained by the three independent variables, while the remaining 33.2% is influenced by other factors not examined in this study.